Boron-based catalysts for C − C bond‐formation reactions - Rao, Bin (2020)
Because the construction of the C−C bond is one of the most significant reactions in organic chemistry, the development of an efficient strategy has attracted much attention throughout the synthetic community. Among various protocols to form C−C bonds, organoboron compounds are not just limited to stoichiometric reagents, but have also made great achievements as catalysts because of the easy modification of the electronic and steric impacts on the boron center. This review presents recent developments of boron‐based catalysts applied in the field of C−C bond‐formation reactions, which are classified into four kinds on the basis of the type of boron catalyst: 1) highly Lewis acidic borane, B(C6F5)3; 2) organoboron acids, RB(OH)2, and their ester derivatives; 3) borenium ions, (R2BL)X; and 4) other miscellaneous kinds.